Kebijakan Lingkungan Terhadap Permasalahan Tambang Pasir di Moro Kepulauan Riau Yang Berdampak Pada Lingkungan Masyarakat Moro - Amalia, Kiki; Dandi, Sri; Wahyuningsih, Yuyun (Public Knowledge, 2024)
Mining activities in the Moro sand of Riau Islands have caused many serious environmental problems, especially damage to marine ecosystems and landscape changes that have an impact on the socio-economic life of coastal communities. This problem is increasingly complex with the government's policy to reopen sea sand export licenses, basically there have also been previous regulations prohibiting the practice. This research aims to analyze the environmental impacts of sand mining and evaluate the countermeasures and regulations implemented by the government. The research method used is a qualitative approach with data collection techniques through document studies, literature, and analysis of related policies. The data obtained is processed through a process of editing, grouping, verification, and descriptive inference to provide an objective picture of the conditions in the field. The results show that sand mining activities in the Riau Islands have an impact on coastal erosion, damage to marine ecosystem habitats, and disruption to the local hydrological cycle. Countermeasures by the government have been carried out through regulations such as Presidential Decree Number 33 of 2002 and Government Regulation Number 26 of 2023. Challenges in regulation implementation and law enforcement remain high, especially related to illegal mining activities and lack of supervisory capacity. Synergy between the government, community, and private sector is needed with the aim of maintaining a balance between economic needs and environmental sustainability. Keywords.Sand Mining, Environment, and Socio-Economic